The additional testsuite framework: facilitating software testing and test management. (15th December 2022) - Sotiropoulos, Panagiotis; Vassilakis, Costas
In this paper, we present the additional testsuite framework, a novel test suite management approach, which provides structures and instrumentation for the creation, maintenance, evolution and use of test suites for software programs. In particular, the tests can be maintained in a centralised repository, and are developed and maintained independently of specific versions of the associated software. Through the use of annotations, tests are categorised and distributed to the desired versions of the software. The presented framework also supports test-based development, dynamic/selective program builds, feature-based builds, testing in different environments and source code analysis. The additional testsuite framework concept has been implemented and extensively evaluated, with the test cases notably including the JBoss EAP CE and OpenLiberty servers.